The Role of Learning Organizations in Nurturing Innovation within Post-Conflict Education - Bashori, Khoiruddin (International Journal of Islamic Educational Psychology, 2025)
This study examines the relationship between innovation capacity and organizational learning in post-conflict Islamic educational settings, focusing on Sukma Bangsa schools in Aceh, Indonesia. It also examines how these schools overcome challenges to implement innovative practices that enhance learning outcomes. Using quantitative and qualitative data from interviews, surveys, and observations, the research highlights collaboration, community engagement, and flexible teaching methods as key drivers of innovation. Data were collected from 120 participants (45 teachers, 15 administrators, and 60 students) via surveys, followed by semi-structured interviews with 20 key informants to deepen contextual understanding. Despite obstacles like resource shortages and trauma, the schools effectively adapt, fostering resilience and creativity. The findings provided broader insights into how organizations in post-conflict contexts can enhance innovation to improve their performance. Beyond education, the study offers valuable lessons for sectors such as healthcare, where similar dynamics may also be applicable. By identifying strategies for adaptation, it underscores the value of an innovation-friendly culture in overcoming adversity. This research contributes to the understanding of the relationship between learning and innovation in conflict-affected environments, providing practical guidance for policymakers and practitioners seeking to enhance resilience in post-conflict recovery efforts.